The Development of Evaluation Model Based on Information Technology and Communication - Larasati, Manik; Prihatin, Titi; Djuniadi, Djuniadi (Universitas Negeri Semarang, 2021)
Implement daily tests at school to find out student capability after learning process on certain materials study. The evaluation model is designed by utilizing technology to achieve expected goals, making it easier to implement and assess daily tests. This research has aimed to (1) analyze students and teachers needs, (2) analyze the design of evaluation model based on ICT, (3) develop an evaluation model that must be applied, (4) assess applicability, (5) evaluating daily tests effectiveness with ICT evaluation model. This research is based on ADDIE research and development model, which covers Analysis, Design, Development, Implementation, and Evaluation. Daily tests so far using paper. Students and teachers need new innovative technology with a username, password, timer, and easy to evaluate. ICT evaluation model has a design with the homepage from WordPress, and then daily tests system use moodle. Based on due diligence from material expert validator, media expert, and practitioner, the ICT evaluation model is feasible to be applied to students. Percentage level validation of small-scale class trials in each aspect is an aspect of the interface, presentation of questions, and advantages with proper assessment results when implemented on a large class scale. Meanwhile, results of large-scale trials in this aspect are feasible if implemented on a larger class scale. Formative evaluation is when the researcher follows up input from the validator. Summative evaluation is carried out after large-scale class trials or activities have ended in their entirety. Evaluation models based on ICT can provide benefits to the education process, especially knowledge about technology for teachers to implement a more varied, flexible, efficient, and effective learning evaluation process that simplifies the assessment process.